Maize Responses to High Night Temperature During Postflowering and Early Grain Filling: Effects on Yield Components, Kernel Growth and Dry Matter Allocation - Kettler, Belén Araceli (2024)
Warm night frequency has increased steadily in the last years across maize production regions, but high night temperature (HNT) effects on growth, grain yield and maize dry matter allocation (DMA) to different plant organs remain poorly understood. In this study, we aimed to (i) analyse the DMA among reproductive and vegetative organs, (ii) evaluate the individual kernel weight through its determinants, rate and duration of grain filling and (iii) quantify changes in grain yield per plant and its components due to HNT during the postflowering and early grain-filling period. Field-grown maize was subjected to HNT induced by shelters during a 15- or 30-day period after silking, encompassing the postflowering period (HNT15) and extending the heating into early grain filling (HNT30), respectively. The HNT was applied from 1900 to 0700 h while control plots remained at ambient night temperature (ANT). Kernel number per plant was decreased under both temperature regimes (i.e., HNT15 and HNT30); however, significant reductions in grain yield were only observed under HNT30. The DMA during the heating period was differentially affected by the duration of heating. While DMA to the stem was likewise reduced by both heating treatments, the partition to the uppermost ear was only reduced under HNT30. Related to the lack of response to HNT treatments of the rate and duration of grain filling, the individual kernel weight was not reduced. The source-sink ratio was not affected by HNT, meanwhile, the apparent reserve use was significantly reduced under HNT30. Our results demonstrate that the magnitude of HNT effects is subjected to the duration of the heating period, but also depends on the intensity of heating explored across seasons, especially for kernel number and grain yield.